Covid-19 Crisis, the New Battleground for the Geopolitics of China and Russia - Raffaele Petroni (Panoply Journal)
The present health crisis is showing the vulnerability of a system that has in China the main world manufacturer. At the same time, it is showing how China and Russia are repositioning on the geopolitical chessboard in the aftermath of the crisis. The strength of their positions will mostly depend on the resilience of the economic and socio-political systems of the most affected countries.